Early occipital injury affects numerosity counting but not simple arithmetic. Issue 1 (2nd January 2016) - Zhang, Han; Chen, Chuansheng; Sun, Zhaohui; Lin, Jiuluan; Zhou, Wenjing; Zhou, Xinlin
Abstract : This study investigated the effects of early occipital injury on the development of counting and simple arithmetic abilities in an occipital epileptic patient. This patient had obvious softening lesions in the bilateral occipital regions due to viral encephalitis at the age of 1.5 years. Results showed that she could perform subitizing and simple arithmetic very well, but could not perform numerosity counting tasks. These results suggest that the occipital cortex plays an important role in the development of numerosity counting skills, but not in the development of subitizing and simple arithmetic.